2018
DOI: 10.1080/14780887.2018.1475532
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide to analysing online support forums

Abstract: As the number of online support forums continues to grow and the amount of user-generated content increases, analysing forum messages can provide researchers and others working in health-related fields with important new insights into the needs, opinions and experiences of individuals who use them. There has been a lack of guidance regarding how to make the best use of user-generated content within forums as a data source in research studies, so this paper explains the practical, ethical and methodological iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 90 publications
0
49
0
Order By: Relevance
“…Due to the consideration needed for what actually constitutes as data within the public domain, and the fact that it could not be confirmed that all users were aware that they were posting and commenting in open groups, authors ensured that only open groups were used and all data remained anonymous to protect users. 76 …”
Section: Methodsmentioning
confidence: 99%
“…Due to the consideration needed for what actually constitutes as data within the public domain, and the fact that it could not be confirmed that all users were aware that they were posting and commenting in open groups, authors ensured that only open groups were used and all data remained anonymous to protect users. 76 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, data held in online forums can provide researchers with the means to access large datasets which have been generated in a naturalistic setting and arguably may get closer to people's real lived experiences. Such research reduces the burden on participants and avoids the artificiality that may result from the intervention of researchers [16]. The objective of the present study was to explore what women say about GDM within online parental support forums for parents.…”
Section: Introductionmentioning
confidence: 99%
“…For the purpose of this study, we draw on the definition by Grady and Gough [ 61 ] of self-management as “the day-to-day management of chronic conditions by individuals over the course of an illness”; self-care is defined as “tasks performed at home by healthy people to prevent illness, rather than merely managing existing illness.” In addition, we will refer to the World Health Organization’s (WHO) International Classification of Functioning, Disability, and Health framework and coding system to assist with the identification of posts related to discrete self-care or self-management tasks and environmental factors [ 62 ]. A record will be kept of the full URL for each thread that is downloaded so that it can be located again if it becomes necessary to refer back to the original webpage during data analysis or subsequent revisions before publication [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…By participating in online discussion boards or forums, members can access a network of individuals facing similar situations, learn from others’ experiences or coping strategies, and share views on self-care and self-management activities in relation to specific health conditions [ 23 , 24 ]. Most discussion forums in online communities are asynchronous, enabling users to post and respond to messages at any time and have a hierarchical structure, containing several distinct message boards arranged thematically [ 25 ]. Each board contains different threads that consist of an initial post through which a member initiates a new discussion by describing an experience, asking a question, or soliciting advice; other members can then contribute by posting replies.…”
Section: Introductionmentioning
confidence: 99%